Sculpture from Zagreb, Medvedgrad and Čazma as Documents of glorious Times - Vjekoslav Jukić (Anastasis: Research in Medieval Culture and Art)
The present article shows the political situation in Northwestern Croatia in the first half of the 13th century, to be more precisely its second quarter. That period is marked by one of the most fascinating phenomena in the Continental Croatian culture of the Middle Ages when this part of Croatia underwent a true local Renaissance in political, economic and cultural spheres. That happened under the aegis of two most capable leaders, Coloman, the son of Andrew II and brother to King Bela IV, and Bishop Stephen II of Zagreb, the former royal Chancellor of Andrew II. Although this rise was cut short by the Tartar invasion of 1241-1242, the little traces that have survived, represent a totally new quality in the Croatian medieval culture. That parts of art production can be seen not only as quality pieces of art, but also as a document, hard evidence that can show the strength and the power of the political and economic programs of Coloman and Stephen II.